2011
DOI: 10.1111/j.1365-3040.2011.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium retention in rice roots is influenced by cadmium availability, chelation and translocation

Abstract: Analysis of rice plants exposed to a broad range of relatively low and environmentally realistic Cd concentrations showed that the root capacity to retain Cd ions rose from 49 to 79%, corresponding to increases in the external Cd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 79 publications
5
122
3
Order By: Relevance
“…Our yeast result is different from two previous studies (Nocito et al, 2011;Satoh-Nagasawa et al, 2012), but consistent with a recent study with HvHMA2, the closest homolog in barley (Hordeum vulgare; Mills et al, 2012). Increased cadmium tolerance by expression of OsHMA2 was very small in the study by Satoh-Nagasawa et al (2012).…”
Section: D-f; Supplementalcontrasting
confidence: 57%
See 1 more Smart Citation
“…Our yeast result is different from two previous studies (Nocito et al, 2011;Satoh-Nagasawa et al, 2012), but consistent with a recent study with HvHMA2, the closest homolog in barley (Hordeum vulgare; Mills et al, 2012). Increased cadmium tolerance by expression of OsHMA2 was very small in the study by Satoh-Nagasawa et al (2012).…”
Section: D-f; Supplementalcontrasting
confidence: 57%
“…3D). Because recent studies reported that OsHMA2 may be implicated in cadmium transport (Nocito et al, 2011;Satoh-Nagasawa et al, 2012;Takahashi et al, 2012), we then also compared cadmium concentration between the mutant lines and wild-type rice. Similar to zinc, the mutant lines contained lower levels of cadmium in the shoots and slightly higher cadmium in the roots compared with the wild-type rice (Supplemental Figs.…”
Section: Mutation Of Oshma2 Resulted In Impaired Delivery Of Zinc To mentioning
confidence: 99%
“…Thus, here, we confirmed that OsHMA3 does not transport Zn. As a whole, the phenotypes of oshma2 OsHMA3-RNAi plants in this study verified the sequential function of OsHMA3 and OsHMA2 in plant; OsHMA3 transports only Cd into vacuoles (Miyadate et al 2011;Ueno et al 2010) and OsHMA2 transports Cd and Zn into the xylem of rice roots (Nocito et al 2011;SatohNagasawa et al 2012;Takahashi et al 2012). Moreover, our results suggest the importance of the complete loss of function of OsHMA2 to minimize Cd translocation from the roots to shoots.…”
Section: Haf1supporting
confidence: 54%
“…On the other hand, insertion mutants resulting in the loss of the function of another heavy metal P-type ATPase in rice, OsHMA2 were used to demonstrate the gene function. OsHMA2 transports Cd and zinc (Zn) into the xylem and is responsible for the translocation of Cd and Zn (Nocito et al 2011;SatohNagasawa et al 2012;Takahashi et al 2012).…”
mentioning
confidence: 99%
“…The synthesis of PCs in response to Cd has been reported in a number of studies conducted on various species including a marine diatom (Thalassiosira nordenskioeldii, Wang and Wang, 2011), freshwater green alga (Scenedesmus vacuolatus, Le Faucheur et al, 2005), tobacco cell culture (Nicotiana tabacum, Zitka et al, 2011), bread wheat (Triticum aestivum, Ranieri et al, 2005), rice (Nocito et al, 2011) and broad bean (Vicia faba, Čabala et al, 2011). The fact that no PCs were detected in the roots of lettuce grown in either Cd treatment indicates that PCs were not involved in Cd 2+ chelation and accumulation in lettuce root.…”
Section: Phytochelatinsmentioning
confidence: 96%